Electronic Properties of Organic Conductors - Mori, Takehiko; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2016)
This book provides an easily understandable introduction to solid state physics for chemists and engineers. Band theory is introduced as an extension of molecular orbital theory, and its application to organic materials is described. Phenomena beyond band theory are treated in relation to magnetism and electron correlation, which are explained in terms of the valence bond theory and the Coulomb and exchange integrals. After the fundamental concepts of magnetism are outlined, the relation of correlation and superconductivity is described without assuming a knowledge of advanced physics. Molecular design of organic conductors and semiconductors is discussed from the standpoint of oxidation-reduction potentials, and after a brief survey of organic superconductors, various applications of organic semiconductor devices are described. This book will be useful not only for researchers but also for graduate students as a valuable reference.
Quantum Chemistry of Molecules -- Quantum Chemistry of Solids -- Transport Properties -- Magnetism -- Electron Correlation -- Superconductivity -- Charge-Transfer Complexes -- Organic Semiconductors.
Keywords: Optical materials; Physical chemistry; Condensed matter; Chemistry, Organic; Optical Materials; Physical Chemistry; Condensed Matter Physics; Organic Chemistry